Siapakah Orang Lain itu? Menafsirkan Lukas 10:25-37 Dari Kacamata Levinas Dan Buber - Taneo, Rolin Ferdilianto Sandelgus (Theologia in Loco, 2023)
Who is the other or my neighbor?  This question is simple but contains a deeper meaning that needs to be reflected upon again.  Commonly, the meaning of the other or neighbors are  still limited to one particular tribe, clan, religion , or identity.  Therefore, this article aims to discover a more inclusive meaning of the other or neighbors t o achieve this goal, the authors will interpret Luke 10:25-37 using narrative and dialogical approaches to find the inclusive meaning of the other or neighbors and bring the narrative into dialogue with the thoughts of two great figures —Emmanuel Levinas and Martin Buber— who offer inclusive views about the other . The author uses the narrative interpretation method to draw meaning from the text into the context of this article. The aim is to offer a view about the other—neighbors or other people who do not share the same identity in order to show that the meaning of the other—some one or people how are different—surpass the shared identity with the self.